Suppression of TGF-β and IL-10 receptors on self-differentiated dendritic cells by short-hairpin RNAs enhanced activation of effector T-cells against cholangiocarcinoma cells - Chutamas Thepmalee (2020)
© 2020, © 2020 Mahidol University. Cholangiocarcinoma (CCA) is an aggressive tumor that is associated with high rates of recurrence and mortality. This is due, in part, to the fact that CCA cells and their microenvironment secrete immunosuppressive cytokines, transforming growth factor-β (TGF-β) and interleukin-10 (IL-10), that inhibit dendritic cell (DC) functions, which, in turn, results in the decreased anti-tumor activity of T-cells. We hypothesized that the TGF-β receptor and IL-10 blockade on dendritic cells would improve DC function, thereby allowing improved activation of T cells against CCA cells. To test our hypothesis, we generated self-differentiated DCs (SD-DCs) via transduction of human peripheral blood monocytes with lentivirus expressing IL-4 and GM-CSF. SD-DCs were transduced with a second lentivirus containing short-hairpin RNAs (shRNAs) to knock-down TGF-βRII and IL-10RA mRNAs. Immunoblot confirmed the reduced expression levels of TGF-β and IL-10 receptors in both SD-DCs that were transduced with a single and/or combination of lentiviruses containing shRNAs. SD-DCs were thereafter pulsed with tumor antigens extracted from CCA cell lines in an effort to activate DC function. MHC class II (HLA-DR) and co-stimulatory molecules (CD40 and CD86) on SD-DCs were upregulated to levels comparable to those on DCs generated by the conventional method. Suppression of TGF-β and IL-10 receptors on SD-DCs influenced the effector T-cells to produce IFN-γ, which enhanced their ability to kill CCA cells. The preparation of adoptive effector T-cells holds the potential of becoming a novel therapy for cellular immunotherapy in CCA.